Evaluation of the anti-Alzheimer's disease activity of N-ferrocenylmethyl-2-nitroaniline using bioinformatics tools - ZEGHEB Nadjiba; BOUBEKRI Cherifa; LANEZ Touhami (University of Eloued جامعة الوادي, 2019)
Inhibition of acetylcholinesterase is currently regarded as the leading strategy against Alzheimer's disease. The principal objective of this project was to investigate the acetylcholinesterase inhibitory activity of N-ferrocenylmethyl-2- nitroaniline (2FMNA) using the bioinformatics tools to predict the relationship between them. In this research, we based on docking study of the interaction between N-ferrocenylmethyl-2-nitroaniline and the AChE by using the open source software AutoDock tools. The X- ray crystal structure of the enzyme AChE (PDB ID :5HF5) were obtained from Protein Data Bank (http://www.rcsb.org./pdb). The N-ferrocenylmethyl-2-nitroaniline structure chosen for docking was optimized with the Gaussian 09 software by the DFT method and the set of B3LYP / 6-311G ++ (d, p) bases. The interaction parameters obtained from molecular docking show that the interaction between 2FMNA and the enzyme is of the electrostatic type.
Intervention
Keywords: N-ferrocenylmethyl-2-nitroaniline; molecular docking; enzyme acetylcholinesterase (AChE); Alzheimer's disease.